Hierarchical partitioning of multiple niche dimensions among ecomorphs, species and sexes in Puerto Rican anoles. (20th July 2022) - Ingram, T.; Giery, S. T.; Losos, J. B.
Abstract: Assemblages of co‐occurring closely related species tend to vary in one or more niche dimensions, but niche partitioning also occurs at levels of biological organization above and below the species level. Niche space occupied by a community may involve variation among groups of species, such as guilds or ecomorphs, and among sexes or individuals within species. We examined variation in structural microhabitat, thermal habitat, and prey size and composition in an assemblage of six anole lizards belonging to three habitat specialist ecomorph categories in a Puerto Rican rainforest. As predicted, ecomorphs were most distinct in structural microhabitat, while species within ecomorphs varied mainly in thermal habitat. Ecological sex dimorphism was limited, and considerable variation in all dimensions was unexplained or potentially related to individual‐level niche variation. Our analysis largely corroborates the view of anole adaptive radiation and community assembly as involving structural habitat divergence among ecomorphs and secondary divergence among species using different climatic niches. A hierarchical approach to niche variation presents opportunities for taking a comparative approach to understanding how ecological diversity is partitioned within communities. Abstract : Ecological diversity within communities can be partitioned above and below the species level. We used hierarchical analyses to confirm how ecomorphs, species and sexes vary across multiple niche dimensions in Puerto Rican anole lizards.